Academic reading under a semantic enhancement environment: An empirical study on users' cognitive load and reading effect. (1st September 2022) - Song, Ningyuan; Chen, Kejun; Jin, Xiufang; Zhao, Yuehua
Abstract: Background: In the digital environment, users' academic reading behaviour has changed, working with many articles simultaneously to search, filter, scan, link, annotate and analyse content fragments. The semantic enhancement environment has been widely set with semantic technologies to offer additional and handy support for users and thus facilitate the reading process. Despite many efforts devoted to developing a semantic enhancement environment, less attention has been paid to its actual effects. Objectives: This study aims to explore the effects of a semantic enhancement environment. Methods: Elaborating on cognitive load theory and focusing on academic reading, this study compared users' cognitive load and reading effect under the semantic enhancement environment and plain text environment and verified the three hypotheses. Results and conclusions: Through experiments and statistical analysis, this study found that, under a semantic enhancement environment, users had their cognitive load reduced and their reading effect improved. Consequently, a semantic enhancement environment promotes academic reading. Takeaways: This study adds to previous literature on semantic publishing by empirically corroborating the conducive effects of semantic enhancement environment in academic reading. Additionally, it justifies semantic publishing and provides a reference for the future design of semantically enhanced reading environments. Lay Description: What is already known about this topic?: The effects of a semantic enhancement environment are open to discuss. Academic reading is fundamental to researches and hence needs promotion. Limited studies investigated the effects of a semantic enhancement environment on academic reading. Publishers require effective reading environment designs. What this paper adds?: This study constructed a semantic enhancement reading environment to conduct a reading experiment. The experiment tested cognitive load, by using WP scale, and reading effects, by answer time and answer score. Semantic enhancement environment reduces users' cognitive load, promotes users' reading effects, and bolsters users' understanding of academic reading materials, especially in microstructure content. The design of semantic enhancement reading environments needs to fully consider the features of reading materials and give users a controllable way of interaction. The implications of study findings for practitioners: Compared to plain text environment, semantic enhancement environment is preferred in academic reading. Publishers are encouraged to add semantic enhancements to their publications. This study discussed how to design an effective learning and reading environment from the perspectives of reading resources, media forms of resources, and interaction modes.